Fierce patriot : the tangled lives of William Tecumseh Sherman - O'Connell, Robert L. (Random House, 2014)
A profile of the iconic Civil War general explores the paradoxes attributed to his character to discuss such topics as his achievements as a military strategist, his contributions to the Transcontinental Railroad, and his tempestuous family relationships.